2012
DOI: 10.1007/s13197-012-0639-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon and nitrogen sources on simultaneous production of α-amylase and green food packaging polymer by Bacillus sp. CFR 67

Abstract: In this paper, effect of different carbon and nitrogen sources, including hydrolysates of rice bran and wheat bran, on simultaneous production of α-amylase (for hydrolysis of starch in food systems) and polyhydroxyalkanoates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 23 publications
0
12
0
2
Order By: Relevance
“…The effect of C/N ratio on PHA yield had also been reported elsewhere [68]. The concept of C/N ratio originated from the biological law according to which limitation of carbon and nitrogen control the molecular size of PHAs and number of bacterial cells.…”
Section: Carbon To Nitrogen Ratiomentioning
confidence: 84%
“…The effect of C/N ratio on PHA yield had also been reported elsewhere [68]. The concept of C/N ratio originated from the biological law according to which limitation of carbon and nitrogen control the molecular size of PHAs and number of bacterial cells.…”
Section: Carbon To Nitrogen Ratiomentioning
confidence: 84%
“…Apart from the carbon, other chemical compounds are required such as nitrogen sources, and some of the most used are (NH 4 ) 2 SO 4 , NH 4 Cl, or NH 4 NO 3 [ 22 ]. Variation in carbon to nitrogen ratios led to a different amount of PHA concentration in bacterial cells [ 38 ], and most of the studies showed that limiting nitrogen concentration while increasing carbon substrates had a positive effect on the PHA production rate [ 39 , 40 ]. Since the biosynthesis process ends with the storage of PHA granules into the cell cytoplasm, a further crucial step is required, the extraction of the PHAs granules from the bacterial cell.…”
Section: Pha: Biosynthesis and Propertiesmentioning
confidence: 99%
“…Biosynthesis of the enzyme was took place not only in the presence of starch but also with other carbon sources (Deb et al, 2013). Production and activity of amylase is increase using tapioca flour as carbon source on medium growth of Bacillus sp (Sreekanth et al, 2013). On the Bacillus tequilensis RG-01, amylase production was increased using wheat bran as carbon source (Tiwari et al, 2014).…”
Section: The Effect Of Different Of Carbon Sourcementioning
confidence: 99%